(untitled) (Dimensión Empresarial, 2020)
Living laboratories are spaces that group research, analysis and experimentation to achieve answers to social, business, technological and environmental problems. For this, a systematic review of the existing literature of the concept was carried out: its origin, characteristics, most important contexts and establish how it relates to innovation. Scientific documents were reviewed from the available academic literature of the different theoretical approaches and it was concluded that with the analysis of the theoretical concept this methodological tool can be understood in its contribution to the innovation processes.